2020
DOI: 10.1371/journal.pone.0236778
|View full text |Cite
|
Sign up to set email alerts
|

Safety, tolerability, and clinical outcomes of hydroxychloroquine for hospitalized patients with coronavirus 2019 disease

Abstract: Background Severe acute respiratory coronavirus 2 (SARS-CoV-2) has caused a devastating worldwide pandemic. Hydroxychloroquine (HCQ) has in vitro activity against SARS-CoV-2, but clinical data supporting HCQ for coronavirus disease 2019 (COVID-19) are limited. Methods This was a retrospective cohort study of hospitalized patients with COVID-19 who received �1 dose of HCQ at two New York City hospitals. We measured incident Grade 3 or 4 blood count and liver test abnormalities, ventricular arrhythmias, and vomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
13
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 24 publications
4
13
2
Order By: Relevance
“…However, COVID-19 and its consequences are still little known, and greater monitoring of these severe ADRs is necessary to better understand this result. In general, our findings corroborate the results of other studies, especially those evaluating the safety of hydroxychloroquine and chloroquine 2,3,4,17 , which identified the association of these drugs and severe ADR, leading to deaths.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, COVID-19 and its consequences are still little known, and greater monitoring of these severe ADRs is necessary to better understand this result. In general, our findings corroborate the results of other studies, especially those evaluating the safety of hydroxychloroquine and chloroquine 2,3,4,17 , which identified the association of these drugs and severe ADR, leading to deaths.…”
Section: Discussionsupporting
confidence: 90%
“…The main sites of manifestation of the reactions we identified are similar to those verified in other studies of ADR in patients with COVID-19: cardiac, gastrointestinal, cutaneous and hepatobiliary systems 15,16,17,21,22 . Prolongation of the QT interval favors the appearance of cardiac arrhythmias, ventricular fibrillation, torsade de pointes and sudden cardiac death 16,22,23 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similarly, Lofgren et al reported a higher frequency of side effects (84%) and medication side effects (27%) among hydroxychloroquine recipients mainly; upset stomach (25% with daily, 18% with twice vs 23% for daily, 16% twice weekly for placebo), nausea (12% weekly, vs 6% for placebo) followed by diarrhoea, vomiting, or abdominal pain (11). This finding was inconsistent with Satlini et al, who found that patients with incident vomiting or diarrhoea were rare (12).…”
Section: Discussioncontrasting
confidence: 64%
“…Several reports did not show improvement in clinical status under chloroquine or HCQ treatment for patients with SARS-CoV-2 infection 21,22,28 . Consequently, these drugs are not approved as first line therapy for SARS-CoV-2 infection in Brazil anymore.…”
Section: Discussionmentioning
confidence: 96%